NAMES IN ARABIC AND ENGLISH (Archive of Conferences, 2020)
Masdar as a verbal name in the grammar of the Arabic language. Gerund as an impersonal verb form. Some aspects of their comparison. As is customary in Arabic grammar, the verbal name in Arabic is called masdar (?? ??????? "Source"), and in English such a name is called -"gerund" (The Gerund).